HUBUNGAN PERSEPSI GURU TERHADAP PROFESI DENGAN KOMITMEN KERJA GURU TK/PAUD DI KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Khairun Nisa; Zulkifli N; Hendar puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Pra survey in TK / PAUD in Kampar Utara Subdistrict, Kampar Regency indicate to have symptoms: (1) teachers who lack preparation in teaching. (2) the existence of teachers who have low morale. (3) lack of work commitment of teachers in carrying out their duties and responsibilities as teachers. (4) the lack of compensation or wages they receive. This study aims To find out the relationship between teacher perceptions of the profession and the commitment of TK / PAUD teacher work in Kampar Utara District, Kampar District. This type of research is quantitative a correlation research approach.The population in this study used was 70 teachers. While the samples used for the trial were 20 teachers, the samples set in this study were 50 people. The data collection technique used is a questionnaire that contains a statement that will be filled by the teacher. The analysis technique data using the product moment correlation formula.The results of this study state that the teacher's work commitment in the high category is 56%, and the moderate category is 44%. The teacher's perception of the profession shows that in the very high category there were 32%, in the high category there were 54%, and the moderate category were 14%. The relationship between teacher perceptions of the profession and the commitment of the work of kindergarten / early childhood teachers in Kampar Utara District, Kampar Regency has a significant relationship. Based on the significance level X and Y smaller than α = 0.05. So variables X and Y have significant correlations. It can be reinforced, the correlation coefficient is 0.476 with a significance of 0.000 in the medium category. Key Words: Perception Profession, Work Commitment